System modules for thermal insulation of residential facilities in the Arctic - Sazonova Yu.; Zhukov A.; Ter-Zakaryan A. (Zenodo, 2017)
About a fifth of the territory of Russia is located in the Arctic, there resides about 1,5 million people and is located about 30 large and medium cities. Another significant factor is the concentration of the territories north of the 67th parallel and mastered a large number of promising deposits of minerals: oil and gas among them. In connection c mining and processing of natural resources necessary to develop construction technologies at extremely low natural temperatures and permafrost.